Characterization of biovar/ races of Ralstonia solanacearum, the incitant of bacterial wilt in solanaceous crops - K.K. MONDAL; RITESH KUMAR JAISWAL, DINESH SINGH*, SHWETA SINHA, D.K. YADAV, J.P. SHARMA, D.K. SRIVASTAVA, H.C. LAL (Indian Phytopathology, 2010)
A survey was conducted to study the status of bacterial wilt of solanaceous crops (potato, tomato, brinjal, chilli and capsicum) caused by R. solanacearum in Northern and Eastern states of India such as Jammu & Kashmir, Himachal Pradesh, Uttarakhand, Jharkhand and West Bengal. Bacterial wilt disease incidence in tomato and chilli was quite low 1 to 3 percent during summer season, whereas in rainy season, it was 4 to 60 percent in tomato and 3 to 40 per cent in brinjal. Disease incidence in tomato crop was more as compared to other solanaceous crops like brinjal, chilli, capsicum, and potato. Eighty four strains of R. solanacearum were collected from all the five states and 65 isolates were used for biovar /race characterization and molecular detection. Out of these 65 isolates, 58 were categorized as biovar 3 and remaining 7 biovar 4. The biovar 3 and 4, causing wilt in solanaceous crops belong to race 1. PCR with R. solanacearum specific primers Y2 (5’- CCCACTGCTGCCTCCCGTAGGAGT-3’) and OLI1 (5’GGGGGTAGCTTGCTACCTGCC3’) were used for molecular detection and all isolates amplified at 288bp. The primer was also able to distinguish the R. solanacearum from other saprophytic bacteria through colony PCR within 2 days.